Saccharides Influence Sperm Quality and Expressions of Motility and Fertilization-Associated Genes in Cryopreserved Sperm of Pacific Abalone, Haliotis discus hannai - Hossen, Shaharior; Sukhan, Zahid Parvez; Cho, Yusin; Choi, Cheol Young; Kho, Kang Hee (Frontiers in Cell and Developmental Biology, 2022)
Pacific abalone, Haliotis discus hannai, is a highly commercial seafood in Southeast Asia. The aim of the present study was to determine the influence of saccharides and vitamin on post-thaw sperm quality, ATP content, fertilization capacity, hatching capacity, and mRNA content of motility and fertilization associated genes of Pacific abalone. Sperm cryopreserved using saccharides improved the post-thaw sperm quality including motility, acrosome integrity (AI), plasma membrane integrity (PMI), and mitochondrial membrane potential (MMP). However, vitamin (l-ascorbic acid) did not result in any significant improvement of sperm quality. Sperm cryopreserved using saccharides also improved ATP content, DNA integrity, and mRNA content of motility and fertilization associated genes of post-thaw sperm than sperm cryopreserved without saccharides. Among sperm cryopreserved using different saccharides, post-thaw sperm quality indicators (except PMI) and mRNA content of motility and fertilization associated genes did not show significant differences between sperm cryopreserved using 3% sucrose (S) combined with 8% dimethyl sulfoxide (DMSO) and sperm cryopreserved using 1% glucose (G) combined with 8% ethylene glycol (EG). However, sperm cryopreserved using 3% S + 8% DMSO showed higher post-thaw sperm quality (motility: 58.4 ± 2.9%, AI: 57.1 ± 3.2%, PMI: 65.3 ± 3.3%, and MMP: 59.1 ± 3.2%), ATP content (48.4 ± 1.8 nmol/mL) and DNA integrity (2.09 ± 0.20%) than sperm cryopreserved using other saccharides. When sperm were cryopreserved using 3% S + 8% DMSO, mRNA content of motility (heat shock protein 70, HSP70; heat shock protein 90, HSP90; protein kinase A, PKA-C; axonemal protein 66.0, Axpp66.0; tektin-4) and fertilization associated (sperm protein 18 kDa, SP18kDa) genes were higher than in sperm cryopreserved using other saccharides. However, changes in mRNA contents of these genes were insignificant between sperm cryopreserved using 3% S + 8% DMSO and 1% G + 8% EG. Taken together, these results indicate that cryopreservation using 3% S + 8% DMSO can improve post-thaw sperm quality and mRNA contents better than other examined cryoprotectants. The present study suggests that 3% S + 8% DMSO is a suitable cryoprotectant for sperm cryopreservation and for molecular conservation of this valuable species.